1983
DOI: 10.1139/b83-104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrastructural analysis of mycorrhizal associations

Abstract: Electron microscopy is a powerful tool in understanding functional mechanisms in symbiosis (i.e., recognition and transfer of nutrients between partners), but mycorrhizal associations are not yet so well known as host–pathogen and host – mutualistic bacterial associations. However, the study of mycorrhizal ultrastructure has provided some interesting information. In fact unknown symbionts can be recognized with electron microscopy and mycorrhizae can be classified according to a sequence linking intercellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
51
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 0 publications
8
51
0
1
Order By: Relevance
“…In host cells with cytoplasmic arbuscules, cytoplasm and cell organelles increase and starch disappears from plastids. This corresponds to the reports on the development of arbuscular host-fungus interactions within roots (Scannerini & Bonfante-Fasolo, 1983) and suggests an active symbiosis with nutrient transfer. Campbell {1908) studied the endophytic fungi in gametophytes of three species of the Gleicheniaceae.…”
supporting
confidence: 90%
“…In host cells with cytoplasmic arbuscules, cytoplasm and cell organelles increase and starch disappears from plastids. This corresponds to the reports on the development of arbuscular host-fungus interactions within roots (Scannerini & Bonfante-Fasolo, 1983) and suggests an active symbiosis with nutrient transfer. Campbell {1908) studied the endophytic fungi in gametophytes of three species of the Gleicheniaceae.…”
supporting
confidence: 90%
“…The functional morphology of cell to cell interactions in vesicular-arbuscular (VA) mycorrhizas is well defined in regard to host/fungus interfaces and cytoplasmic organelles (for reviews see Scannerini & Bonfante-Fasolo, 1983;Bonfante-Fasolo & Gianinazzi-Pearson, 1986;Bonfante-Fasolo, 1987, 1988GianinazziPearson & Gianinazzi, 1988). However, the patterns of the host cell nuclei remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As the penetrating hypha enters the cortical cell, the plant plasma membrane is not breached but invaginates and is then extended to form the periarbuscular membrane (Cox and Sanders, 1974;Bonfante-Fasolo, 1984;Toth and Miller, 1984). Transmission electron microscopy (TEM) studies showed accumulation of cytoplasm and organelles, including endoplasmic reticulum (ER), Golgi bodies, plastids, and mitochondria, in the area around arbuscule branches (Cox and Sanders, 1974;Scannerini and Bonfante-Fasolo, 1982). In addition, the tonoplast invaginates, and the TEM micrographs revealed the presence of multiple small vacuole compartments (Cox and Sanders, 1974;Toth and Miller, 1984), which led to the interpretation that arbuscule development is accompanied by fragmentation of the plant central vacuole (Scannerini and Bonfante-Fasolo, 1982;Bonfante and Perotto, 1995;Gianinazzi-Pearson, 1996;Harrison, 1999).…”
mentioning
confidence: 99%
“…Transmission electron microscopy (TEM) studies showed accumulation of cytoplasm and organelles, including endoplasmic reticulum (ER), Golgi bodies, plastids, and mitochondria, in the area around arbuscule branches (Cox and Sanders, 1974;Scannerini and Bonfante-Fasolo, 1982). In addition, the tonoplast invaginates, and the TEM micrographs revealed the presence of multiple small vacuole compartments (Cox and Sanders, 1974;Toth and Miller, 1984), which led to the interpretation that arbuscule development is accompanied by fragmentation of the plant central vacuole (Scannerini and Bonfante-Fasolo, 1982;Bonfante and Perotto, 1995;Gianinazzi-Pearson, 1996;Harrison, 1999). Immunolocalization studies showed that arbuscule development is accompanied by reorganization of plant cytoskeletal components that surround the developing arbuscule and likely directs membrane deposition and organelle accumulation Bonfante, 1997, 1998;Blancaflor et al, 2001).…”
mentioning
confidence: 99%